Pediatric Capitellum Fracture Fixation with Bio-absorbable K-wire - Fawaz Mohammed Manu; M Jyothi Prasanth; Hijas Ismayil (Journal of Orthopaedic Case Reports)
Introduction: Pediatric capitellum fractures are rare, accounting for <1% of elbow fractures in children. They are typically caused by axial loading on an outstretched arm. Due to the high cartilaginous composition of the pediatric elbow, these fractures are often missed in radiographic diagnosis. Proper diagnosis using computed tomography or magnetic resonance imaging is essential for effective treatment planning. Case Report: A 14-year-old female sustained a left elbow injury following a fall while playing. Clinical and radiological evaluations confirmed a displaced Hahn–Steinthal fracture of the capitellum. Open reduction and internal fixation using bio-absorbable K-wires were performed. Postoperatively, an above-elbow cast was applied for 4 weeks. At 10 weeks, the patient had achieved a full range of motion, and radiographic assessment confirmed fracture union. Conclusion: Pediatric capitellum fractures, though rare, can lead to significant morbidity if not diagnosed and treated in a timely manner. The use of bio-absorbable K-wires offers an effective fixation method, eliminating the need for a second surgery for implant removal. Early intervention, proper radiological assessment, and surgical management result in excellent functional outcomes with minimal complications.